Controlled one pot synthesis of polyoxofluorovanadate molecular hybrids exhibiting peroxidase like activity - Nicolaou, Maria; Drouza, Chryssoula; Keramidas, Anastasios D. (My University, 2019)
Three unique mixed-valence polyoxofluorovanadate clusters have been synthesized through a facile preparation process. The structure of these clusters is controlled by the addition of organic ligands. Single-crystal X-ray diffraction revealed that the clusters have the formula (XyH2)4[VV10VIV4O14(μ-O)10(μ3-O)10(μ3-F)2F4] (1), (Xy = m-xylylenediamine), (pyH)4(H)2[VV10VIV2O12(μ-O)8(μ3-O)10(μ3-F)2(pic)2] (2) and (pyH)4(H)3(Na+)[VV7VIV2O9(μ-O)8(μ3-O)4(μ5-F)(pic)4]2 (3), (py = pyridine, pic− = picolinate), with 2 and 3 representing the first examples of polyoxofluorovanadate clusters coordinated to a chelating ligand. The electron paramagnetic resonance (EPR) spectroscopy of 1 revealed that the spins of the VIV centers are coupled to each other, in contrast to the isolated spins of the isostructural [VV12VIV2O16(μ-O)10(μ3-O)10(μ3-F)2(L)2]6−, where L: im = imidazole (4); py (5). The trigonal bipyramidal coordinated VV atoms of 1, 4 and 5 mimic the structure of the active site of the vanadium dependent peroxidases and 4 and 5 exhibit peroxidase like activity.
Keywords: Bis(Acetylacetonato)Oxovanadium(IV); Vanadium Compounds; Oxovanadium IV